Mimicking the Dynamic Mechanical ECM Using Engineered Biomaterials to Investigate Cellular Crosstalk - Banani Kundu (Proceedings)
The stiffness of a tissue changes during the lifetime of an individual and is an indicator of age, disease, and pathophysiological conditions [...]